Ahmad Sanusi’s Rauḍah al-‘Irfān fī Ma’rifah al-Qur’ān - Rifa Tsamrotus Sa’adah (Qur'an and Hadith Academic Society, 2019)
This study discusses Ahmad Sanusi’s Rauḍah al-‘Irfān fī Ma’rifah al-Qur’ān, By using a descriptive analytical method, this study finds that Sanusi uses simple language to explain the message of Quran, so that the local community could easily understand the Quran, he is also one of the figures who has moderate thinking, and on the other hand he maintained the understanding of Shafi’i scholars in his book.